The role of the private sector in providing gap housing in Johannesburg - Coetzee, Gerrit (My University, 2018)
South Africa has a significant housing shortage and even though the government has provided in excess of three million subsidised houses to beneficiaries since 1994, a shortage of 2.1 million units still exists. While households earning less than R3 500 qualify for a fully subsidised house, the most affordable newly built house on the market in Johannesburg is only affordable to households earning about R14 300. Therefore, a gap in the housing market exists between those too rich to qualify for a full housing subsidy and those too poor to access formal bonded housing. A partial subsidy, called the Finance-Linked Individual Subsidy Programme (FLISP), is available to households earning less than R15 000 to help them access housing in the formal market. Although private developers are developing houses affordable to households earning less than R15 000, uptake of the subsidy has been limited. Johannesburg has roughly 385 000 households in the gap market. This study seeks to establish what role the private sector currently plays in providing gap housing in Johannesburg. A qualitative study was done by interviewing various developers who are involved with gap housing developments, using semi-structured interviews and email correspondence. Furthermore, this study aims to establish what perceptions developers have of the market, what difficulties they face, what barriers exist to entering the market and how private companies help their employees in accessing gap housing. It was found that developers have a positive view of the market. Many echoed the view that the market in Johannesburg is vast, growing and that there are plentiful opportunities. There are, however, factors that make delivering less expensive houses more difficult. Bulk service contributions, especially, are becoming excessive, while the time taken to approve new townships can lead to unnecessary holding costs. Poor access to development finance is seen as prohibiting new developers from entering the market. Developers are aware of only a handful of private companies involved with assisting their employees to access gap housing. Although there are numerous gap housing developments in Johannesburg and many more planned, relatively few FLISP subsidies have been granted. These subsidies are tied to access to traditional mortgage finance. Fewer and fewer mortgages in the gap housing range have been given in recent years and if more houses are to be delivered, housing finance should be made more accessible to lower income earners.
A research report submitted to the faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements of the degree of Masters of the Built Environment in Housing. Johannesburg, 2018
Keywords: Low-income housing--South Africa; Housing--South Africa